Komatiites of the Ukrainian Shield - Usenko, O. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Ultramafic volcanic rocks are formed as a result of lifting the primary melt formed at a depth of 250 km. In the Archean, the oxidized chloride-water-silicate fluids were active. With their participation, komatiites were formed and compose the greenstone structure of the Srednepridneprovsky megablock. Igneous rocks of the Middle Bug were formed with the participation of the alkali fluoride carbonate fluids, active in the Paleoproterozoic. It is not possible to attribute them to the komatiitic formation.